Application of the Adomian decomposition method and Laplace transform method to solving the convection diffusion-dissipation equation - Yindoula, Joseph Bonazebi; Pare, Youssouf; Bissanga, Gabriel; Bassono, Francis; Some, Blaise (International Journal of Applied Mathematical Research, 2014)
In this paper, the Adomian decomposition method and Laplace transform method are used to construct the solution of a convection-diffusion-dissipation equation.